Library and information science (LIS) and its related fields as viewed and applied in knowledge management environments in selected government agencies in the Philippines - Zambale, Jerome Paul P.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2012)
Knowledge management (KM) is an internationally emerging field in the Library and Information Science (LIS) profession and it has created new opportunities and challenges to the skills and competencies of library and information professionals. However, the LIS profession in the Philippines seems to be afar from what is happening in the global scenario. Due to this, the researcher took an interest to investigate the LIS roles, skills and competencies are applied and viewed in some KM environments in the country. The study sampled a KM expert through Dr. Serafin Talisayon who is known as the "Father of KM in the Philippines", and government agencies through the KM programs of the National Economic Development Authority (NEDA), Department of Health (DOH), and the House of Representatives, all of which have started to engage in KM in the early 2000s.
The LIS skills, based from the foreign studies of Abell and Oxbrow, Morris and Todd and Southon, applied in the said government agencies come from Information Management (IM) and Information Technology (IT) competencies. According to the respondents coming from these government agencies, for LIS professionals to effectively work under KM environments, further training in KM that provides KM literacy and competencies are required aside from IM and IT skills. Furthermore, there is an existing view on libraries as repositories for documented knowledge among these different government agencies and their respective KM programs. In connection to this, even with training in KM, IT, and enhanced IM skills, librarians are still expected to perform traditional library-oriented tasks based from the core competencies they have.
Implications of this study for the LIS profession and education include changing the name of the program itself, and re-evaluate the curriculum for both undergraduate and graduate courses; further training and education should be taken by librarians and LIS students not only in KM, but also in their chosen fields of specialization within the LIS domain; and intensify campaigns that promote the better image of librarians and modern librarianship not only among the students and in the academe, but more importantly among future employers who are unaware of the skills and competencies that librarians possess nowadays. To further improve the research, a follow-up study should be done among multinational companies as these organizations have a different organizational culture and their view on librarianship and librarians in KM may be different as compared from the views of government agencies. Lastly, this study also raised the idea of conducting a nationwide study among different employers which would determine their perspectives on the LIS profession.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Knowledge management; Administrative agencies -- Philippines; Government information agencies -- Philippines